Реакційна здатність пероксильних радикалів із заміщеними біс(N-фенілантранілатами)-кальцію - Суховєєв, О.В.; Ковтун, Г.О.; Суховєєв, В.В. (Видавничий дім "Академперіодика" НАН України, 2008)
The interaction rate constants of peroxide radicals of ROO˙ (R = C6H5CH(CH3), C6H5(CH3)2C, H) with the NH-bond of complex CaL2: [2-(4-X-C6H4NH)C6H4COO]2Ca (X = H, CH3, tert .-C4H9, C6H5, Cl, CN) (k1, l/mol·s) are measured at 70–90 ºС. It is shown that the values of k1 do not depend on the structure of a substituent R in the radical ROO˙ and are determined by the electronic distribution of an NH-bond. The reaction rate constants of radicals of C6H5CH(CH3) with CaL2 grew in the line of increasing the electron-donor characteristics of substituents X: CH3 > tert .-C4H9 > C6H5 > H > Cl > CN. The obtained coefficient of linear correlation ρ = −1.5 of lg k1 and the σ^+ constants of substituents X in CaL2 corresponds to the realization of a polar transient state of the reactions under study.